Epistemological Beliefs and Writing Self-Efficacy as Predictors of Second Language Writing Anxiety: A Structural Equation Modeling Approach - Heidarzadi, Mohamad; Barjesteh, Hamed; Nasrollahi Mouziraji, Atefeh (Frontiers in Psychology, 2022)
This study was carried out to investigate the roles of epistemic beliefs (EBs) and writing self-efficacy (WSE) in predicting second language writing anxiety (L2WA) among learners of English as a foreign language (EFL). To this end, three validated scales were distributed among 240 EFL students. They were asked to complete the questionnaires during their regular courses. A structural equation modeling (SEM) approach was utilized to analyze the hypothesized SEM model and the causal paths among the constructs. The direct and indirect path analyses of the hypothesized model indicated that EBs and WSE accounted for 43% of the variance in L2WA. Although both constructs (i.e., EBs and WSE) had a significant effect on L2WA, EBs turned out to be a robust predictor of increasing L2WA. Notably, it was revealed that learners’ EBs directly and significantly influenced their L2WA. Besides, the results indicated that WSE had a unique effect in reducing L2WA. More precisely, students who had a higher level of EBs seemed to have a greater L2WA, and those who had a higher level of WSE experienced less L2WA. The findings of this explanatory study suggest that L2 teachers and material developers should pay serious attention to the Students’ cognitive and affective variables as they were known to be significant factors in influencing L2WA.